ChemInform Abstract: Semiconducting Black Phosphorus: Synthesis, Transport Properties and Electronic Applications. Issue 27 (18th June 2015) - Liu, Han; Du, Yuchen; Deng, Yexin; Ye, Peide D.
Abstract Review: 92 refs.